A challenging breast cancer type; Differentiation to neuroendocrine tumors - Yıldız, Ömer Serdar; Başak, Fatih (Journal of Surgery and Medicine, 2017)
Aim:Neuroendocrine type breast carcinomas are rarely observed. Most of these tumorsare seen as cell-differentiated neuroendocrine breast carcinoma but with all thisinfrequency, there is also a rarer type which is called as pure neuroendocrinebreast carcinoma. The common locations for neuroendocrine tumors are lung andgastrointestinal system (stomach and pancreas). Although estimations vary, theannual incidence of clinically significant neuroendocrine tumors isapproximately 6.5-5 per 500,000; two thirds are carcinoid tumors and onethird are other neuroendocrine tumors. The estimated prevalence is 35 per100,000. In this article, we analyze the patients admitted with breast problemsand had the diagnosis of breast cancer with neuroendocrine differentiation orpurely neuroendocrine tumor. Methods: Retrospective cohort study is designed to review neuroendocrinebreast cancer patients. Female patients with pathological examination which haveneuroendocrine components in neoplasm were reviewed. Demographics, preoperativeimaging, diagnostic evaluations, operation and pathological examination recordsof patients were recorded. Results: Neuroendocrinebreast cancer was observed in 11 patients in study period. All patientsreceived standard therapy like non-specific breast cancer. Only two of 11 patients(18%) were diagnosed with neuroendocrine differentiation in preoperative periodby biopsy. One patient received neoadjuvant treatment. Modified radicalmastectomy was performed in eight patients (72.8%). Breast conserving surgerywas performed in remaining three patients. Conclusion: Neuroendocrinebreast cancer is rare entity, and diagnose at preoperative period may bechallenging. In most casesthe correct diagnosis is made after proper examination of the postsurgicalspecimen. Future studies for specific treatments would be of interest.